The Fabrication of ZnO Nanoparticles-Modified Carbon Paste Electrode for the Analysis of Nicotine Content in E-Cigarette Liquids by Cyclic Voltammetry - Fatihah, Vita Ayu; Setiarso, Pirim (Indonesian Journal of Chemical Research, 2024)
ZnO nanoparticles were used as composites on carbon paste working electrodes to enhance electrode performance in the analysis of nicotine content in e-cigarette liquids by voltammetry cyclic. The optimum composition and condition (pH and scan rate) were determined to identify the conditions that gave the best response. ZnO nanoparticles were synthesized using the sol-gel method and characterized by FTIR, XRD, and SEM. The determination of optimum composition and conditions was studied using cyclic voltammetry. The determination of nicotine content in e-cigarette liquids was analyzed by cyclic voltammetry. The electrode composition that gave the best response was 3:5:2 (carbon: nanoparticles ZnO: paraffin). The optimum conditions for nicotine determination by cyclic voltammetry were at pH 8 and a scan rate of 90 mVs-1. The cyclic voltammetry’s limit detection (LoD) using a ZnO nanoparticles-modified carbon paste electrode is 0.00678 mg/mL, and the percent recovery is 100.35%.